Enhancing the referral process for surgical management of spinal metastases: insights from a 12-year, bi-institutional study of 533 patients - Debono, Bertrand; Perez, Alexis; Lonjon, Guillaume; Hamel, Olivier; Dandine, Jean-Baptiste; Dupuy, Martin; Dutertre, Guillaume; Braticevic, Cécile; Latorzeff, Igor; Amelot, Aymeric (Frontiers in Oncology, 2024)
Delayed surgical management of spinal metastases (SMs) can have detrimental effects on patient survival and quality of life, leading to pain and potential neurological impairment. This study aimed to assess the impact of delayed referral for SMs on clinical outcomes by analyzing patients managed in emergency situations.We retrospectively reviewed the data of all patients admitted on either emergency or elective basis who underwent surgery for the treatment of neoplastic spine lesions at our two institutions (tertiary referral neurosurgical units) between January 2008 and December 2019.We analyzed 210 elective (EGp) and 323 emergency patients (UGp); emergencies increased significantly over the 12-year period, with a Friday peak (39.3%) and frequent neurological impairment (61.6% vs. 20%).Among the UGp patients, 186 (7.5%) had a previously monitored primitive cancer, including 102 (31.6%) with known SMs. On admission, 71 of the 102 (69.9%) patients presented with neurological deficits.UGp patients were more likely to undergo a single decompression without fixation. Outcomes at the 3-month follow-up were significantly worse for UGp patients ([very] poor, 29.2 vs. 13.8%), and the median overall survival for UGp patients was statistically lower. Risk factors for patients with SM undergoing emergency management included short delay between onset of symptoms and first contact with a spine surgeon, and an initial motor deficit.Many patients with previously identified metastases, including those with neurological deficits, are urgently referred. Optimization is needed in the oncology pathway, and all stakeholders must be made aware of the factors contributing to the improvement in the clinical and radiological identification of potential complications affecting patient survival and quality of life.